Formação continuada de professores de Ciências da Natureza de classes ribeirinhas multisseriadas da Amazônia com base na Teoria Antropológica do Didático - Santos, Silvia Lima dos (2022)
This study is part of Teacher Education in the Amazon context, whose main objective was to analyze the interrelationships of formation continued of teachers of Nature Sciences, in multiseriat riverside classes, with the teaching práxis, from the Moments of Study of the Anthropological Theory of the Didactic (TAD). Through the continuous training we seek to highlight the process of Internal Didactic Transposition (TDI) in teachers' practices, visualizing the way they organized their plans of class before training and during development, that is, in the process of constructing the text-know, as well as in the management of their Praxeological Organizations, in action in the classroom. In the light of the TAD we investigate how to constitute continuing training of riverine teachers of Natural Sciences of the multiseriat classes based on the moments of study of TAD so that it occurs an interrelationship with the teaching praxis? The study is anchored in an articulation between the areas of Science Education, Continuing training of teachers and multiseriiat classes, based on the theoretical thinking of Zeichner (2008) and Paulo Freire (2020). It is a qualitative approach study, based on the reference of Esteban (2010), theoretical and methodological assumptions are based on the Anthropological Theory of the Didactic by Yves Chevallard (1999). The construction of the data took place from two steps: the first corresponds to the "Pre-action" Connection which consisted of the researcher entering the field of research, its first articulations, contacts with teachers, and planning for conducting the research process as a whole. The second stage corresponds to the cycle of reflective studies that includes the five collective Formative Meetings held with teachers in the city of Urucurituba, visits to schools together with reflective sessions, together, they represent an overview of the path of research. The analyses show the cultural universe of the professor from the Amazon and reveals a triad from the Institutions (Teacher, Community and School) as responsible for the movement of educational reality from riverside communities. They show that the continued formation made possible the visualization of the Internal Didactic Transposition (TDI) process carried out by/the teachers/as. Signal the presence of cultural/Amazonian knowledge in the Praxeological Organisations of/the teachers/as, point to two categories "in the field" and "field in the field" and reveal the complexity of teaching in Amazonian multiseriat classes. Thus, the study culminates in maintaining that continued training of teachers to this reality should be conducted based on a human, ethical, political formation, with respect to the local cultural universe and for social justice. Keywords: Praxeologies. Sciences of the Nature. Multisseriat. Professor riverside. Social Justice.